Pengaruh Display Product Dan Discount Terhadap Impulsive Buying Pada Produk Rabbani (Survei Pada Konsumen Rabbani Di Kota Tasikmalaya): - Solihah, Ulia Inayatu; Pauzy, Depy Muhamad; Oktaviani , Nita Fauziah (Jurnal Pakar Manajemen, 2024)
This research aims to determine the effect of Product Display and Discount on Impulsive Buying of Rabbani Products. The method used is quantitative with a research sample of 100 respondents. The data used are primary and secondary data. The analytical tool used in this research is multiple linear regression analysis using SPSS version 25. Based on the results of this research, it shows that Product Display and Discount simultaneously have a positive and significant effect on Impulsive Buying of Rabbani Products. Product Display partially has a significant effect on Impulsive Buying. Discounts partially have a significant effect on Impulsive Buying.